Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s12070-011-0404-6
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of ‘Otological Injury Secondary to Head Trauma’

Abstract: The aim of study was to evaluate etiological factors, types of skull fracture and associated hearing loss in 50 cases of head injury. This was prospective study involving 50 cases of head injury. Each patient will be subjected to detailed history, otological and neuro otological examination, radiological study followed by audiological assessment by pure tone audiometry. Road traffic injuries were the most frequent cause of injuries in our patients comprising 64% of the total, personal accidents/ domestic falls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 5 publications
(5 reference statements)
1
15
0
2
Order By: Relevance
“…Among patients in group B, 19 complained of tinnitus, 8 of ear fullness, and 6 of hearing disturbance. Singh et al [12] reported hearing disturbance in 21 out of 50 patients, with head injury and tinnitus in 12 patients. The prevalence of hearing disturbance in our study group was lower, presumably because we excluded patients with temporal bone fracture or intracranial lesions, who might have been more likely to have had severe head trauma.…”
Section: Discussionmentioning
confidence: 98%
“…Among patients in group B, 19 complained of tinnitus, 8 of ear fullness, and 6 of hearing disturbance. Singh et al [12] reported hearing disturbance in 21 out of 50 patients, with head injury and tinnitus in 12 patients. The prevalence of hearing disturbance in our study group was lower, presumably because we excluded patients with temporal bone fracture or intracranial lesions, who might have been more likely to have had severe head trauma.…”
Section: Discussionmentioning
confidence: 98%
“…Singh et al in their study found that out of 9 cases of fracture of the petrous part of the temporal bone, longitudinal fracture was present in 7 (78%) and transverse fracture in 2 (22%) cases. 8 Chamyal in their study of 50 head injury cases, reported 22 cases (44%) of skull fracture, out of which 14 (28%) had fracture temporal bone on further breakdown. 9 Out of these in temporal bone patients 10 (72%) had longitudinal and 4 (28%) had transverse fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Depressed skull fractures may require surgery to lift the bones off the brain if they are pressing on it by making burr holes on the adjacent normal skull. 1 In a depressed skull fracture, the outer table of one or more of the fracture edges lies below the normal anatomical level of the inner table as determined by the surrounding intact skull. 2,3 At the site of impact mostly the inner table fracture first and get depressed inside.…”
Section: Introductionmentioning
confidence: 99%